2006
DOI: 10.1373/clinchem.2005.064857
|View full text |Cite
|
Sign up to set email alerts
|

The Antibody Configurations of Cardiac Troponin I Assays May Determine Their Clinical Performance

Abstract: Background:Previous studies have shown superior clinical performance of the cardiac troponin I (cTnI) assay from Beckman-Coulter Diagnostics. This assay had a unique combination of monoclonal antibodies with 2 monoclonal antibodies directed against epitopes near the NH 2 terminus of the heart-specific region of troponin I. The approach has been adopted by the new cTnI assay from Abbott Diagnostics. The aim of our study was to investigate whether this approach affects the clinical performance of cTnI assays. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
47
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 21 publications
4
47
0
2
Order By: Relevance
“…Discussion cTn values above the 99th percentile are known to be strong predictors of early adverse events in those with ACS (4,8,(15)(16)(17). This study, in concordance with the prior studies of Venge and colleagues, probed values below the 99th percentile (4,8,9 ).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Discussion cTn values above the 99th percentile are known to be strong predictors of early adverse events in those with ACS (4,8,(15)(16)(17). This study, in concordance with the prior studies of Venge and colleagues, probed values below the 99th percentile (4,8,9 ).…”
Section: Resultssupporting
confidence: 90%
“…This study, in concordance with the prior studies of Venge and colleagues, probed values below the 99th percentile (4,8,9 ). Using the same assay (AccuTnI), Venge et al (4 ) reported that the 99th percentile for cTnI was Ն0.02 g/L in a young, healthy population.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Several research groups used one of these assays to determine the levels of HNL/NGAL in urine and drew the conclusion that HNL/NGAL is a biomarker of AKI (12,13,16 -18). Our previous results indicated that the antibody configuration had an effect on the clinical performance of the assay (19,25). We also reported, for the first time, the existence of several molecular forms of HNL/NGAL in urine obtained from patients after cardiac surgery and that the presence of dimeric and monomeric forms and their ratios changed after operation (19).…”
mentioning
confidence: 79%
“…The classification outlined above is seemingly robust and easy to communicate but is weakened by its lack of consideration of the actual clinical performance characteristics of assays. In previous reports, we have shown that cTnI assays of similar analytical sensitivities had very different clinical performance for outcome prediction depending on the antibody configurations of the assays and possible autoantibody interferences (5)(6)(7). To reemphasize this point, we have reevaluated the VIDAS cTnI assay and compared the clinical performance of this assay in a head-to-head comparison with 2 current laboratory assays, the Access AccuTnI and Architect cTnI assays, and with 2 pointof-care tests (POCTs), the i-Stat and Stratus CS cTnI assays.…”
mentioning
confidence: 99%